2017
DOI: 10.1177/0162643417729166
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Assistive Technology for Individuals With Intellectual Disability in the Workplace

Abstract: Research has shown that assistive technology (AT) can help support employment skills for individuals with intellectual disabilities (IDs). The authors of this review examined the effectiveness of various types of AT support for individuals with ID in the workplace with a focus on the participant’s independent ability to demonstrate a specific employment skill. Ten articles published between 2006 and 2016 met inclusionary criteria set forth for this review. Overall, AT support resulted in medium to highly effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…Furthermore, findings highlight the use of assistive technology in enhancing work participation by facilitating the completion of certain work tasks and performance of responsibilities. With rapidly developing technological solutions, putting in place technology-based accommodations (applications, software) has become readily available [41], making the implementation of such accommodations more practical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, findings highlight the use of assistive technology in enhancing work participation by facilitating the completion of certain work tasks and performance of responsibilities. With rapidly developing technological solutions, putting in place technology-based accommodations (applications, software) has become readily available [41], making the implementation of such accommodations more practical.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental supports were also identified; an accessible work environment in which accommodations were made to meet the employee's needs, optimized performance and facilitated engagement in the workplace [30,38]. Many employees reported working from home [25,33,38] and using assistive technology such as Dictaphones, dual monitors, assistive devices for communication and computerized phones and alarms, positively impacted work satisfaction and work maintenance [33,[39][40][41].…”
Section: Products and Technology/natural Environment And Human-made Cmentioning
confidence: 99%
“…Tau-U. Tau-U has become one of the more commonly used measures of ES today due to its nonparametric approach (Morash-MacNeil et al, 2018;Parker, Vannest, Davis, & Sauber, 2011). Tau-U is derived from Kendall's and Mann-Whitney U (see Parker et al, 2011) and is calculated by merging trend and nonoverlap data.…”
Section: Discussionmentioning
confidence: 99%
“…AT is a resource that has repeatedly demonstrated the ability to help individuals with ID gain independence across various aspects of their lives and is capable of reducing the dependence upon others to promote independence within the workplace (Cihak, Kessler, & Alberto, 2008). Recent reviews found AT was successful for increasing work performance of individuals with ID in the workplace in respect to productivity, navigation, time management, and task completion (Collins & Collet-Klingenberg, 2017; Morash-MacNeil, Johnson, & Ryan, 2018). AT that includes evidence-based techniques, such as videos as prompting tools or task analysis, has been shown to increase job task performance and completion, while decreasing the number of prompts required by a job coach (Van Laarhoven, Johnson, Van Laarhoven-Myers, Grider, & Grider, 2009).…”
Section: Effective Employment Supportsmentioning
confidence: 99%
See 1 more Smart Citation